2006
DOI: 10.1103/physrevlett.96.205502
|View full text |Cite
|
Sign up to set email alerts
|

Density of Vibrational States of a Hyperquenched Glass

Abstract: The vibrational density of states of a hyperquenched and an annealed glass has been measured using nuclear inelastic scattering. The hyperquenched sample shows a higher number of vibrational states in the low-energy region with respect to the annealed glass. It reveals, however, lower density and sound velocity and, therefore, smaller Debye energy. After rescaling the energy axes in Debye energy units and area renormalization, the density of states of both samples becomes identical. Thus, the effect of quenchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
66
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 25 publications
13
66
3
Order By: Relevance
“…Without exception, available results are all in agreement [3,4,[13][14][15][16][17][18][19][20][21][22]: the BP shifts towards higher frequencies and decreases in intensity when the sample becomes stiffer (increase of elastic constants). Recently, it has been proposed to quantitatively test the role played by the changes in the elastic properties by scaling the BP data with the Debye frequency, a quantity defined by the elastic medium.…”
Section: Introductionsupporting
confidence: 65%
“…Without exception, available results are all in agreement [3,4,[13][14][15][16][17][18][19][20][21][22]: the BP shifts towards higher frequencies and decreases in intensity when the sample becomes stiffer (increase of elastic constants). Recently, it has been proposed to quantitatively test the role played by the changes in the elastic properties by scaling the BP data with the Debye frequency, a quantity defined by the elastic medium.…”
Section: Introductionsupporting
confidence: 65%
“…In addition, a strong boson peak in C p /T 3 had already been observed by us in (20 million years old) Dominican amber [10], though apparent residual curing or repolymerization, occurring around the glass transition temperature when rejuvenating those amber samples, hindered a reliable quantitative investigation. Although some authors have tried to correlate the boson peak feature in glasses [38], and even in crystals [39], with transformations of the elastic continuum only, such a Debye-scaling rule is not hold quantitatively in our case. The height of the C p /T 3 boson peak in the hyperaged amber has decreased a 22% from the standard rejuvenated glass, whereas a Debye scaling [38] 3 (, D with D being the Debye frequency) would predict only a 7.4% reduction.…”
Section: Discussionmentioning
confidence: 42%
“…Although some authors have tried to correlate the boson peak feature in glasses [38], and even in crystals [39], with transformations of the elastic continuum only, such a Debye-scaling rule is not hold quantitatively in our case. The height of the C p /T 3 boson peak in the hyperaged amber has decreased a 22% from the standard rejuvenated glass, whereas a Debye scaling [38] 3 (, D with D being the Debye frequency) would predict only a 7.4% reduction. Unfortunately, a similar discussion on the boson peak in ultrastable glasses of indomethacin is not possible since this feature is hardly seen in the specific-heat curves of this glass.…”
Section: Discussionmentioning
confidence: 42%
“…8,9 Experimentally the BP has been studied as a function of macroscopic parameters such as the temperature, 10,11 the density, [12][13][14][15] and the pressure 16,17 or during chemical vitrification 18 or as a function of the quenching rate. 19 It is observed that the BP shifts to higher frequencies and decreases in intensity when the pressure or the density is increased. However, controversial results have been reported on the connection between the BP modification and the change in the elastic medium properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, controversial results have been reported on the connection between the BP modification and the change in the elastic medium properties. In some systems, 14,18,19 it appears that the BP variation is solely associated with the change in the Debye frequency, which accounts for the modifications of the elastic continuum medium. In other cases, 13,[15][16][17] the BP shifts more strongly than suggested by the simple variation of the macroscopic medium.…”
Section: Introductionmentioning
confidence: 99%